Knowledge-Network-Based Inter-institutional Collaborative Teaching of Translation - Mu, Yuanyuan; Yang, Wenting (Learning Technologies and Systems, 2021)
Knowledge Network plays an essential role in translation teaching and learning, especially assisted with e-learning approaches and data-driven design. This paper focuses on inter-institutional co-construction of knowledge network for translation learning facilitated by Textwells, an online platform for translation teaching and learning. Translation teachers from five universities in China have participated in inter-institutional collaborative teaching of translation by adopting the knowledge network derived from the Textwells Platform and designing an online teaching template together in the 2020 spring semester during the COVID-19 pandemic. With this online collaborative teaching experience shared in a national-wide webinar, a short online survey has been conducted afterwards to investigate the perception of knowledge-network-based teaching among a group of teachers briefly trained for this new teaching approach. Therefore, it has been proved that knowledge-network-based collaborative teaching is deemed effective and will be applied to translation teaching and learning more widely in the future.